Examining the impact of credibility and quality on electronic word-of-mouth (eWOM) and visit intention of tourists to culinary tourism destinations - Heri Setiawan; Rini Rini; Astika Ulfah Izzati; Ilham Prawidi Sakti; Dika Setiagraha; Septi Kumala Putri; Claudia Nurcahya (Jurnal Manajemen dan Pemasaran Jasa, 2023)
This study aims to examine the relationship between source credibility, message reliability, information quality, and visit intention to culinary tourism. Additionally, it assesses the mediating role of eWoM in relation to the variables investigated. Local tourists who are acquainted with culinary tourism destinations in Palembang City are the focus of the study. A purposive sampling methodwas used to select the respondents, resulting in the distribution of 180 participants evenly across 5 culinary tourism destinations in Palembang, namely the 26 Ilir, Kuto, Kapitan Village, Kuto Besak Fortress, and Kambang Iwak. The study used structural equation modeling (SEM) with the Maximum Likelihood (ML) estimation method to evaluate the proposed model. The results showed that source credibility can enhance eWoM, while message reliability and information quality do not have the same effect. Furthermore, eWoM can stimulate the intention of visitors to participate in culinary tours and strengthen the relationship between the variables. This study provides empirical insights that can assist culinary tourism managers in understanding the intention of visitors to participate in eWoM. Source credibility, message reliability, and the provision of high-quality information play crucial roles in determining the intention of visitors to partake in eWoM. Consequently, culinary tourism managers should ensure the continuous satisfaction of visitors to prevent the spread of negative eWoM on social media.